In the red : a novel - Shapiro, Elena Mauli (Little, Brown and Company, 2014)
"When Irina--Romanian by birth but brought up by American parents who have never understood her--arrives at college she quickly abandons ordinary student life for an affair with an older, mysterious Romanian man named Andrei. Andrei awakens a powerful sensuality in Irina. And he has money--lots of it. For the first time, Irina feels free. But the longer she stays with Andrei, the more she is certain that she can't leave, and that [she] may be complicit in Andrei's work--whatever that 'work' might be"--Amazon.com.